Comparative Analyses of Complete Peronosporaceae (Oomycota) Mitogenome Sequences—Insights into Structural Evolution and Phylogeny. (14th April 2022) - Winkworth, Richard C.; Neal, Grace; Ogas, Raeya A.; Nelson, Briana C. W.; McLenachan, Patricia A.; Bellgard, Stanley E.; Lockhart, Peter J.
Abstract: Members of the Peronosporaceae (Oomycota, Chromista), which currently consists of 25 genera and approximately 1, 000 recognized species, are responsible for disease on a wide range of plant hosts. Molecular phylogenetic analyses over the last two decades have improved our understanding of evolutionary relationships within Peronosporaceae. To date, 16 numbered and three named clades have been recognized; it is clear from these studies that the current taxonomy does not reflect evolutionary relationships. Whole organelle genome sequences are an increasingly important source of phylogenetic information, and in this study, we present comparative and phylogenetic analyses of mitogenome sequences from 15 of the 19 currently recognized clades of Peronosporaceae, including 44 newly assembled sequences. Our analyses suggest strong conservation of mitogenome size and gene content across Peronosporaceae but, as previous studies have suggested, limited conservation of synteny. Specifically, we identified 28 distinct syntenies amongst the 71 examined isolates. Moreover, 19 of the isolates contained inverted or direct repeats, suggesting repeated sequences may be more common than previously thought. In terms of phylogenetic relationships, our analyses of 34 concatenated mitochondrial gene sequences resulted in a topology that was broadly consistent with previous studies. However, unlike previous studies concatenated mitochondrial sequences provided strong support for higher-level relationships within the family.